Pemanfaatan Biochar dan Pupuk Kandang Ayam pada Pertanaman Jagung Hibrida di Tanah Ultisol - Samsul Bahri; M Merismon; S Sutejo (JURNAL GALUNG TROPIKA, 2020)
This study aims to evaluate the growth and production of hybrid maize on ultisol soils using biochar and chicken manure to support sustainable agriculture. This study used a factorial design based on the randomized block design, which consisted of two treatment factors and three replications. The first factor is the dosage of biochar consisting of 4 levels, namely without biochar (control), 0.25 kg.m-2; 0.5 kg.m-2; and 1 kg.m-2. The second factor is the dose of chicken manure, consisting of four levels, namely without chicken manure (control), chicken manure with a dose of 0.25 kg.m-2; 0.5 kg.m-2; and 1 kg.m-2. The results showed that biochar treatment had a significant effect on plant height. The interaction between treatments has a significant effect on the weight of the ear without the cob. The best biochar treatment was at a dose of 0.25 kg.m-2 while the best treatment of chicken manure was at a dose of 1 kg.m-2.